2020
DOI: 10.21470/1678-9741-2020-0283
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass Graft During the COVID-19 Pandemic

Abstract: Since the beginning of the coronavirus disease (COVID-19) pandemic, in March 2020, the number of people infected with COVID-19 worldwide increases continuously. Brazil is being followed with great concern in the international media, as it can, very soon, be the epicenter of the pandemic. Initial surgical data suggest that patients who acquire COVID-19 in the perioperative period are prone to a higher morbidity and mortality, however, evidence in cardiac surgery is still scarce. This article aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…The COVID-19 is not supposed to disappear but remains among us as another endemic viral disease, also pending if immunity after the SARS-CoV-2 infection or a vaccine will lead to effective and lasting protection. For the cardiovascular surgeon, the decision of the appropriate surgical moment became even more sensitive in times of COVID-19 pandemic, where delays add significantly to the burden of the disease [ 24 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 is not supposed to disappear but remains among us as another endemic viral disease, also pending if immunity after the SARS-CoV-2 infection or a vaccine will lead to effective and lasting protection. For the cardiovascular surgeon, the decision of the appropriate surgical moment became even more sensitive in times of COVID-19 pandemic, where delays add significantly to the burden of the disease [ 24 ] .…”
Section: Discussionmentioning
confidence: 99%
“…9,10 It has been reported that patients who underwent cardiac surgery during 2020 have been infected with COVID-19, and that patients with CVD are more likely to have a severe presentation of SARS from COVID-19. 11 Another major concern is that patients with CVD disease are afraid to call emergency assistance or go to emergency rooms for fear of contracting COVID-19 or burdening an already-overwhelmed health-care system. 12 One possible explanation to the increase in death rate is that in most of the time only emergency surgeries were allowed, characterizing more severe patients.…”
Section: Discussionmentioning
confidence: 99%
“…Combining this with the predilection of SARS-CoV-2 to cause microvascular pathology suggests that free-flap reconstructions may face unique challenges with concurrent SARS-CoV-2 infection. Several case studies have described remarkable surgical site complications in the setting of SARS-CoV-2 infection [13][14][15]. Benmoussa et al described the failure of a chimeric thoracodorsal artery perforator flap and a free fibula flap performed for gingival mandibular squamous cell carcinoma, and da Silveira et al describe significant sternal dehiscence following a coronary artery bypass graft [14][15].…”
Section: Discussionmentioning
confidence: 99%